Teknik Penerjemahan dalam Antologi Puisi Kidung Saka Bandungan - PRESSANTI, DESI ARI (Kementerian Sekretariat Negara Republik Indonesia, 2016)
Poetry translation is relatively more difficult than any other literary translation, since the translator is expected to be capable of sending the message without diminishing the aesthetic value of the source text. To that end, the translator should have an exceptional mastery of both the source and target languages as well as the ability to employ various translating techniques. For this reason, this research deals with an analysis of the techniques used in translating poems from the anthology “Kidung Saka Bandungan”. The aims of this research are to: (1) provide a description and explanation on poetry translation, especially from Javanese into Indonesian; and (2) provide references to translators about the techniques of translation. This research uses the descriptive-qualitative method. The results show that the translator uses some techniques in translating poems, they are the addition, omission, transposition, modulation, culture equivalence, and borrowing techniques. Key words: poetry, translation, technique in translation.